Open-Cell Foam Metal Production and Characterization by Aluminum Solid Mold Investment Casting - Guler, Kerem Altug (CRC PRESS-TAYLOR & FRANCIS GROUP, 2019)
Foam metals can be categorized in two basic classes: open-cell and closed- cell structures, which both have different numerous unique properties. Up to the present, several production processes have been developed for each class.Investment casting is known as a replication process for opencell foam metal fabrication.Solid mold, which can be evaluated as a subtechnique of the investment casting, is specialized especially for small complex shapes with ultrathin sections. This work is a presentation of aluminum open-cell foam production with solid mold investment casting using two different kinds of patterns.The first one is burnable, in which liquid metal directly fills the shape of pattern and the second is leachable, in which metal takes the form of intergranular network shape of porous salt preforms.
Keywords: Aluminum; Foam metal; Investment casting; Open-cell; Solid mold; Materials Science; Metallurgy & Metallurgical Engineering